The Biology of Eosinophils and Their Role in Asthma - McBrien, Claire N.; Menzies-Gow, Andrew (Frontiers in Medicine, 2017)
This review will describe the structure and function of the eosinophil. The roles of several relevant cell surface molecules and receptors will be discussed. We will also explore the systemic and local processes triggering eosinophil differentiation, maturation and migration to the lungs in asthma, as well as the cytokine-mediated pathways that result in eosinophil activation and degranulation, i.e. the release of multiple pro-inflammatory substances from eosinophil specific granules, including cationic proteins, cytokines, chemokines growth factors and enzymes. We will discuss the current understanding of the roles that eosinophils play in key asthma processes such as airway hyperresponsiveness, mucus hypersecretion and airway remodelling, in addition to the evidence relating to eosinophil-pathogen interactions within the lungs.